A person-specific perspective on the dynamics of anxiety in foreign language learning: A dynamic P-technique factor analysis - Elahi Shirvan, Majid; Taherian, Tahereh; Kruk, Mariusz; Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2025)
In the field of second and foreign language (L2) anxiety studies, which are predominantly group-based, the role of individual-level inner workings of L2 anxiety has been neglected. Emerging evidence in L2 learning underscores that while aggregating data from a large number of learners reveals general trends, this approach often overlooks the distinct characteristics inherent in each individual’s data. For this reason, specialists have emphasized the necessity of illuminating unique and individualized experiences of L2 anxiety, both in short- and long-term evaluations. The present study aimed to grasp person-specific variation in L2 anxiety in Sara, an adult female L2 learner. In a year-long ecological momentary assessment study design, Sara provided daily replies to an online questionnaire about L2 anxiety. Using the dynamic P-technique, this research explored how Sara’s L2 anxiety ratings on a given day impacted or predicted her rating on the following day and the consistency of her evaluations over time. Results revealed that a four-factor structure best represented her daily L2 anxiety, comprising lack of self-confidence (LSC), fear of negative evaluation (FNE), performance anxiety (PA), and negative attitude toward language learning (NA). It was observed that on days when Sara experienced higher-than-usual LSC and FNE, her return to equilibrium was slower compared to days with heightened PA or NA. Additionally, despite daily fluctuations in the four subfactors, these factors appeared immune to fluctuations in predictor levels and did not immediately affect other subfactors. Moreover, LSC, FNE, PA, and NA exhibited positive feedback loops, where each subfactor could potentially predict another in subsequent states.